Carbon Nanotube Ink Dispersed by Chitin Nanocrystals for Thermoelectric Converter for Self‐Powering Multifunctional Wearable Electronics. Issue 33 (6th October 2022) - He, Yunqing; Lin, Xiaoying; Feng, Yue; Luo, Binghong; Liu, Mingxian
Abstract: The screen‐printing process of conductive ink can realize simple and large‐scale manufacture of micro/nano patterns for producing wearable electronic products. Herein, chitin nanocrystals (ChNCs) are used as a dispersant for the preparation of multiwalled carbon nanotube (MWCNT) ink with high viscosity and uniformity by ultrasound treatment. ChNCs can interact with MWCNT in noncovalent ways, including π – π and hydrophobic interactions. ChNCs/MWCNT (CCNT) ink does not aggregate even after standing for 3 months with a maximum MWCNT concentration of 33 mg mL −1 and dispersion efficiency of 91.1%. Using CCNT ink, a paper‐based thermoelectric generator (TEG) is manufactured by screen‐printing technology. With good thermoelectric and strain sensing properties, CCNT coated paper can stably collect human energy at room temperature to realize self‐powering. The CCNT coated paper‐based TEG can convert thermal voltage signals into musical notes, monitor the changes in human behavior and respiratory rate, and monitor joint movements. Moreover, CCNT coated paper has no cytotoxicity by CCK‐8 and live/dead staining. This work puts forward a strategy of green preparation of MWCNT‐based ink by adding renewable chitin, which opens up a new way to apply MWCNT‐based ink in self‐powering wearable multifunctional sensors. Abstract : A stable and biocompatible multiwalled carbon nanotube ink stabilized by chitin nanocrystals is prepared, in which the two nanoparticles can interact via π – π and hydrophobic interactions. The conductive ink is coated on paper by screen‐printing technology to obtain the paper‐based thermoelectric generator, which shows multifunctional applications in self‐powering wearable sensor.